Didactic Analysis of Junior High School Students Mathematical Literacy Skill on Space and Shape - Faizatunnisa,; Tayeb, Thamrin; Syah, Fazya Auliyah; Khaerani, Fahrizah Nurul; Saraswati, (Alauddin Journal of Mathematics Education, 2023)
It is important for learners to have mathematical literacy skills because it can help learners utilize mathematics in real life, solve problems, assess whether the results obtained make sense, and analyze situations and make conclusions. In the Program for International Students Assessment (PISA), there are four mathematics contents: Space and Shape, Change and Relationship, Quantity, and Uncertainly and Data. The purpose of this study is to identify the learning obstacles experienced by students in the Space and Shape content. This study used a qualitative approach using dedactical design research. With 16 learners, this research was conducted at SMP PST Guppi Samata class IX. The instruments used in data collection are tests and non-tests. The test material consists of questions about mathematical literacy skills level 3, 4, and 6 using flat-sided space building material. The non-test instruments used in collecting data are observation and documentation. Based on the research results, students experience learning difficulties in space and shape content which causes them to be less able to evaluate solutions that have been interpreted. The percentage shows that out of 16 students in class IX, 10% of them have high math ability, 60% have medium math ability, and 30% have low math ability. Efforts can be made to start with the habituation of providing basic calculations so that students can answer test questions correctly. After that, motivation can be given and encourage students to be enthusiastic in understanding the concept of critical thinking in applying the context of the problem to real objects.